65 CORONARY ARTERY BYPASS GRAFTING AS A PRECIPITATING FACTOR IN DIABETIC KETOACIDOSIS IN TYPE 2 DIABETES. (1st January 2006) - Sehgal, V.; Kitabchi, A.
Abstract : A 56-year-old woman with type 2 diabetes (T2DM) presented with unstable angina. ECG showed ST elevation in all leads. On admission, she developed VTAC followed by asystole and was resuscitated with transvenous pacing. Angiogram showed triple-vessel disease. Preoperatively the patient was on insulin lispro of 4.5 U/hr with subcutaneous (SC) dose of sliding scale insulin every 2 hours. On the day of surgery, her fasting blood glucose was 180 mg/dL with no ketone or abnormal electrolytes. She received 6 U of lispro SC and was premedicated 1 hour before surgery and was preoxygenated. Anesthesia was induced with thiopentone, morphine, isoflurane, and vecuronium. Postinduction blood glucose was increased to 463 mg/dL with HCO3 of 15.1, pH of 7.25, and urine ketone of 3+. The patient received IV dose of 10 U of lispro and 25 mL of 7.5% HCO3 . The following table depicts the patient's treatment during surgery and postoperatively with responses to therapy. She also received 100 mL (20%) of mannitol as a prophylaxis for possible hypercoagulation state. The patient recovered uneventfully. Her insulin requirement postoperatively was 2 U/h on average blood glucose of 118-170 mg/dL with normal electrolytes. The patient was discharged 5 days later. We conclude that anesthesia induction and coronary artery bypass grafting (CABG) in this T2DM patient resulted in the emergence of diabetic ketoacidosis (DKA) in which hydration, low to moderate dose of insulin, and frequent monitoring of the patient resulted in uneventful recovery from DKA.